2012
DOI: 10.1080/15389588.2011.633235
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Crashes of 16- to 17-Year-Old Drivers Involving Alcohol, Nighttime Driving, and Passengers

Abstract: Stronger night and passenger restrictions with increased compliance and greater application of alcohol-specific policies would likely be effective in reducing the alcohol-related and non-alcohol-related crashes of 16- to 17-year-olds. Increasing the licensing age beyond age 16 would supplement the effectiveness of these actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…It has been reported that for drivers aged 15-20 years, a greater percentage of their fatal motor vehicle collisions occur at night, without the use of seat belts, and with positive BACs, relative to other age groups (92). Williams et al (93) recently reviewed the circumstances of fatal motor vehicle collisions between drivers aged 16 and 17 years and concluded that alcohol-positive drivers were "more likely than those in nonalcohol-related crashes to be male, unbelted, in single vehicles, and speeding, and their collisions were more likely to have occurred on Saturday or Sunday, at night, and when passengers were present" (93). Such analyses demonstrate the risk-taking behavior that is inherent to crash risk in young drivers; behavior that may be exacerbated by the presence of alcohol.…”
Section: Agementioning
confidence: 99%
“…It has been reported that for drivers aged 15-20 years, a greater percentage of their fatal motor vehicle collisions occur at night, without the use of seat belts, and with positive BACs, relative to other age groups (92). Williams et al (93) recently reviewed the circumstances of fatal motor vehicle collisions between drivers aged 16 and 17 years and concluded that alcohol-positive drivers were "more likely than those in nonalcohol-related crashes to be male, unbelted, in single vehicles, and speeding, and their collisions were more likely to have occurred on Saturday or Sunday, at night, and when passengers were present" (93). Such analyses demonstrate the risk-taking behavior that is inherent to crash risk in young drivers; behavior that may be exacerbated by the presence of alcohol.…”
Section: Agementioning
confidence: 99%
“…The relevance of this restriction is supported by the observation that the risk of a fatal accident at night is approximately twice as big as during the day [32]. Research also shows that a ban on driving at night is indirectly targeted at alcohol-related accidents: 88% of all alcohol-related accidents among 16-and 17-year olds happen at night and/or with passengers in the vehicle [33].…”
Section: Impact Of Gdl Componentsmentioning
confidence: 99%
“…Researchers have also considered, specifically, the effect of age and gender variables on the accident rate (Begg, Langley and Stephenson 2003;Chen et al 2010;Williams et al, 2012) and their interaction with some of the risk factors. The relevance of these variables in explaining the differences in the tendency to take risks, perception of risk and the accident rate is highlighted, identifying a greater tendency to take driving risks in young people and people aged over 60, compared to middle age adults.…”
Section: Introductionmentioning
confidence: 99%